FokI POLYMORPHISM OF VITAMIN D RECEPTOR (VDR) GENE ON PULMONARY TUBERCULOSIS PATIENTS IN BALI, INDONESIA - Artini, I Gusti Ayu (Innovare Journal of Life Sciences, 2019)
ABSTRACT Â Objectives Nowadays tuberculosis still become major health problem in Asian country including Indonesia. The response of tuberculosis treatment is affeccted by many factors including Vitamin D Receptor (VDR) gene polymorphism. Several polymorphism on VDR gene was reported in several studies responsible for treatment response or susceptibility to tuberculosis infection, one of which was FokI polymorphism. The distribution of FokI VDR genotype is highly affected by race and ethnicity. So far there has been no study about this in Bali. Therefore, it is very important to conduct this study to identify the proportion of FokI VDR polymorphism in tuberculosis patients in Bali, Indonesia. Â Methods This study was a cross sectional study. As many as 35 subjects were selected from adult pulmonary tuberculosis patients who came to pulmonary outpatient clinic of Sanglah Hospital, Bali. Analysis of FokI VDR polymorphism was using PCR/RFLP technique by using restriction enzyme FokI. Â Results The proportion of FF, Ff, and ff genotype in this study were 20%, 54.3% and 25.7%, respectively. Â Conclusions The dominant genotype of VDR in pulmonary tuberculosis patients in Bali was Ff. Â Keywords: FokI polymorphism, vitamin d receptor, susceptibility, treatment, tuberculosis